Human rights of people with disability: some legal and ethical considerations (2016)
All human beings have the rights to life and dignity as persons, but with disabilities (PWDS), often experience human rights violations and exclusion from the mainstream of society. Exclusion and segregation against persons with disabilities occurs in forms ofobvious discrimination such as the denial of educational opportunities. It can also occur in more subtle forms such as segregation and isolation resulting from the imposition of physical and social barriers. Effects of disability- based discrimination have been particularly severe in fields such as education, employment, housing, transport, cultural life and access to public places and services. Terms like distinction, exclusion, restriction, preference, or denial of reasonable accommodation on the basis of disability, are words that describe the treatment of PWDS, which negatively affect and impact on the recognition, enjoyment or exercise of the rights of persons with disabilities. Law, therefore, as a system of social engineering, has a lot of potentials to address these social trends which directly negate the human rights of PWDS in all areas of life. This paper examines the relevant legal issues for the realisation of the rights of PWDS including legislative provisions and policies, human rights protection and promotion and the place of affirmative action. The methodology used in this paper is the in-depth content analysis of primary sources in form of relevant legal instruments and other secondary sources in the form of relevant textbooks, journal articles, electronic materials and others. First, various forms of rights violations or denials leading to abuses are discussed and documented. The paper also shows that disability affects people irrespective of race, colour, gender, political or religious inclinations and that PWDS are generally vulnerable to being discriminated against and excluded from the mainstream of society. The paper concludes that the law, if well enacted and enforced, is capable not only of redressing discrimination against PWDS, but by affirmative action, it can create a level playing ground by mandating certain steps which will engender the protection and promotion of the rights of PWDS in Nigeria